Genetic diversity in natural Cupressus sempervirens L. populations in Turkey - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
Nine polymorphic out of 13 isoenzymes (Gdh-A, Lap-A, Mdh-B, Mdh-C, Ndh-A, 6Pgd-B, Pgi-B, Pgm-A and Pgm-B) were used to assess genetic diversity in seven natural Cupressus sempervirens populations in South-western Anatolia. Except for Pgi-B, all loci were in Hardy-Weinberg equilibrium. A high level of genetic diversity was observed within populations. The mean number of alleles was 2.3 +/- 0.08, the effective number of alleles was 1.53 +/- 0.10, the percentage of polymorphic loci was 82.6 +/- 8.7%, expected heterozygosity was 0.350 +/- 0.039, observed heterozygosity was 0.326 +/- 0.039, and the fixation index was 0.049. Interpopulation differentiation was moderate, with differentiation indices of G(ST) = 0.073 and delta = 0.104. A UPGMA tree and differentiation (D-j) showed that Kumluca, Kemer and Kas were the most differentiated populations. Pgm-B was one of the loci contributing most to interpopulation differentiation (G(ST) = 0.119; D-i = 0.201), clearly distinguishing Eastern populations, as indicated by a highly significant correlation coefficient between D-j and longitude (R-2 = 0.88**). No other significant correlation was found between genetic measures and geographical traits for the Turkish cypress populations. A metanalysis of these and other cypress populations from Crete and the Aegean islands, that had been characterised previously using the same isoenzymes, showed no significant relationship between altitude and genetic measures (within-population differentiation or delta(T), observed heterozygosity, fixation index and D-j). Observed heterozygosity and latitude were negatively correlated. Longitude was found to be correlated with heterozygosity, fixation index and differentiation. Genetic and geographic distances were positively correlated over loci. Deviations from selective neutrality by Ewens-Watterson test were observed for Pgm-B, Ndh-A and 6Pgd-B. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: Cupressaceae; conifer; isoenzymes; population variation; geographical trends; genotype environment interaction; DIFFERENTIATION; ALLOZYME